COMORBIDITY IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE: A ROLE OF CARDIOVASCULAR DISORDERS - N. A. Karoli; A. P. Rebrov (Рациональная фармакотерапия в кардиологии)
Aim. To study prevalence and features of cardiovascular diseases (arterial hypertension, ischemic heart disease, chronic heart failure) in patients with chronic obstructive pulmonary disease (COPD).Material and methods. 233 patients with COPD (229 men, 4 women; 55,3±0,6 y.o.) were examined. General clinical examination, including body mass index calculation, 6-min walk test, blood analysis, electrocardiography, echocardiography, investigation of respiratory function, pulsoxymetry was carried out. Cardiac Infarction Injury Score (CIIS) index was also evaluated.Results. COPD is associated with arterial hypertension in 62,2% of cases, ischemic heart disease - 27%, carotid atherosclerosis - 43,6%, chronic heart failure in 23,6% of cases. Risk factors of ischemic heart disease in COPD patients include: age, COPD severity, bronchial obstruction severity (decrease of forced expiratory volume), systemic inflammation (high level of C-reactive protein). Patients with severe and very severe COPD had CIIS index >20 1,8 times more often than patients with moderate COPD. Significant correlation of CIIS index with pulmonary hypertension (r=0,21, p<0,05), end-diastolic dimension of right ventricle (r=0,24, p<0,05) and left ventricle (r=0,33, p<0,05), left ventricle ejection fraction (r=-0,40, p<0,01) was found.Conclusion. COPD is associated with cardiovascular diseases. CIIS index can help to detect previous myocardial infarction in COPD patients.